2006
DOI: 10.1210/en.2005-1051
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Arcuate Nucleus Communicates Peripheral Metabolic Information to the Suprachiasmatic Nucleus

Abstract: The arcuate nucleus (ARC) is crucial for the maintenance of energy homeostasis as an integrator of long- and short-term hunger and satiety signals. The expression of receptors for metabolic hormones, such as insulin, leptin, and ghrelin, allows ARC to sense information from the periphery and signal it to the central nervous system. The ventromedial ARC (vmARC) mainly comprises orexigenic neuropeptide agouti-related peptide and neuropeptide Y neurons, which are sensitive to circulating signals. To investigate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(112 citation statements)
references
References 63 publications
4
107
1
Order By: Relevance
“…It has been reported that the blood-brain barrier border could actually lie at the area between the median eminence and the distal part of the arcuate, indicating that the proximal arcuate could be exposed to circulating neuroactive substances (Shaver et al, 1992). Recently, a reciprocal linkage between the ventromedial arcuate to the SCN was established by means of anterograde and retrograde tracing techniques (Yi et al, 2006). Thus, the fact that the SCN receives an input from the arcuate suggests at least an indirect communication between the general circulation and the SCN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the blood-brain barrier border could actually lie at the area between the median eminence and the distal part of the arcuate, indicating that the proximal arcuate could be exposed to circulating neuroactive substances (Shaver et al, 1992). Recently, a reciprocal linkage between the ventromedial arcuate to the SCN was established by means of anterograde and retrograde tracing techniques (Yi et al, 2006). Thus, the fact that the SCN receives an input from the arcuate suggests at least an indirect communication between the general circulation and the SCN.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin may also be synthesized in the hypothalamus (for review, see Horvath et al, 2001). Ghrelin-immunoreactive neurons are present in the paraventricular, dorsomedial, ventromedial, and arcuate nuclei, areas important for circadian output (Cowley et al, 2003;Yi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…LH-NPY rats, however, consume as much food in the light phase as in the dark phase, probably because of induced wakefulness (Szentirmai and Krueger, 2006). Interestingly, the suprachiasmatic nucleus, which drives the diurnal rhythm of feeding activity, is hypothesized to accomplish this via projections to the LH (Abrahamson et al, 2001), but also direct projections from the suprachiasmatic nucleus to the arcuate nucleus are present (Yi et al, 2006). A continuous stimulation by increased NPY signaling in the LH would therefore explain the increased anticipation to eat as well as the time spent feeding.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may also provide an explanation as to why in early studies lesioning the ventro medial hypothalamus resulted in diminished FAA, which recovered in time (44,45). We have not studied the effect of DMH lesion for periods longer than 6 wk, but it is possible that over time, the strength of other inhibitory inputs to the SCN [e.g., from the arcuate nucleus (46)] may increase and thus result in recovery of FAA consequent to an increase in inhibitory input to the SCN. Because we have observed a similar mechanism for arcuate-SCN interaction (47), we would like to propose that this is a general feature for hypothalamic structures, allowing them to impose adaptive changes depending on the requirements of the body.…”
Section: Faa Is Lost After Lesion Of the Dmh But Reappears After Amentioning
confidence: 94%